Atypical Presentation of Antisynthetase Syndrome: A Case Report - Shalesh Rohatgi; Prajwal Rao; Satish Nirhale; Pravin Naphade (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Antisynthetase syndrome is characterized by autoantibodies against one of many aminoacyl transfer RNA synthetases. The clinical features include interstitial lung disease (ILD), non-erosive arthritis, Raynaud’s phenomenon, myositis, unexplained fever, and/or mechanic’s hands. There is higher incidence of ILD compared to polymyositis or dermatomyositis. Antisynthetase syndrome associated with Pl-7 and Pl-12 antibodies is rare and accounts for less than 10% of all cases. We present a case of 63-year-old lady who presented with only polymyositis without any ILD or other features of antisynthetase syndrome and was positive for anti Pl-7 and anti Pl-12 antibodies.